Concepts for Nano-delivery of Therapeutic Immunomodulatory Agents - Italiani, Paola; Boraschi, Diana (Current Bionanotechnology (Discontinued), 2016)
Nanotechnologies in medicine play a growing role in the development of innovative vaccines and therapeutic immunomodulatory agents. By varying their composition, size, shape, and surface properties, it is possible to obtain a vast range of nanocarriers highly efficient in targeting specific organs, tissues or cells for diagnostic and therapeutic purposes. Antibodies, anti-inflammatory drugs, adjuvants, DNA, proteins and peptides can be loaded on nanocarriers and delivered to target sites, overcoming limitations associated with recognition by innate immune cells (phagocytes), bio distribution, physical barriers, and so on. Recent evidence has highlighted the involvement of the inflammatory response in the pathogenesis of many different diseases (from neurodegeneration, autoimmunity and atherosclerosis to respiratory diseases, chronic inflammatory diseases and cancer) and on the pivotal role of macrophages. On this basis, new nanodrugs are being designed, able to specifically modulate the functional activity of these immune cells. Macrophage polarisation/plasticity and macrophage “memory” are key immunological functions in health and disease that could be modulated by innovative nanodelivery systems for preventive and therapeutic strategies.
Keywords: immunotherapy